2024
DOI: 10.3390/molecules29020327
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Electrochemical Sensors for Formaldehyde

Yufei Yang,
Yuanqiang Hao,
Lijie Huang
et al.

Abstract: Formaldehyde, a ubiquitous indoor air pollutant, plays a significant role in various biological processes, posing both environmental and health challenges. This comprehensive review delves into the latest advancements in electrochemical methods for detecting formaldehyde, a compound of growing concern due to its widespread use and potential health hazards. This review underscores the inherent advantages of electrochemical techniques, such as high sensitivity, selectivity, and capability for real-time analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 184 publications
(215 reference statements)
0
0
0
Order By: Relevance
“…On the other Molecules 2024, 29, 2772 2 of 14 hand, electrochemical sensors have the advantages of low cost, simplicity, sensitivity, and on-the-spot detection. Intensive studies have been devoted to exploiting high-performance formaldehyde electrochemical sensors [9][10][11]. For instance, Yinuo Zhang et al reported a formaldehyde electrochemical biosensor based on the selective electrochemical oxidation of formaldehyde catalyzed by aldehyde dehydrogenases (ALDHs) on a Cu electrode, with a limit of detection (LOD) of 1.46 × 10 −15 M [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other Molecules 2024, 29, 2772 2 of 14 hand, electrochemical sensors have the advantages of low cost, simplicity, sensitivity, and on-the-spot detection. Intensive studies have been devoted to exploiting high-performance formaldehyde electrochemical sensors [9][10][11]. For instance, Yinuo Zhang et al reported a formaldehyde electrochemical biosensor based on the selective electrochemical oxidation of formaldehyde catalyzed by aldehyde dehydrogenases (ALDHs) on a Cu electrode, with a limit of detection (LOD) of 1.46 × 10 −15 M [9].…”
Section: Introductionmentioning
confidence: 99%